Reference intervals for thyroid-stimulating hormone in the adult Lebanese population: Results from the last decade - Elie Naous; Riam Hijazi; Marianne Chalhoub; Nada El Ghorayeb; Marie-Hélène Gannagé-Yared (Heliyon)
Background: Thyroid Stimulating Hormone (TSH) is the most accurate marker in the assessment of thyroid function. Establishing a reference interval (RI) for TSH is essential for interpreting results of thyroid function tests. TSH RI in the Lebanese population using the indirect method is lacking. The aim of this study is to establish TSH RI according to age and gender, and to assess its trend over the last decade using the indirect method. Methods: TSH values of 80156 outpatient subjects (age range 18–99) were retrospectively collected between January 2011 and April 2021 from a tertiary university medical center in Beirut. TSH was measured using the same chemiluminescent assay (Immulite 2000). Results: The median TSH was 1.4 mIU/L (IQ 0.94–2.10). TSH RI was wider compared to the manufacturer one (0.31–4.95 mIU/L vs 0.40–4.0, p < 0.001). There was a decrease in lower reference limit (LRL) and an increase in upper reference limit (URL) with the increase in age categories (p < 0.001 for both comparisons). RI was broader in women compared to men (respectively 0.29–5.20 vs 0.35–4.48 mIU/L, p < 0.001). There are significant differences in the median, LRL and URL across the years and in all age categories (p < 0.001). TSH RI using the indirect method was wider than the direct method one (p < 0.001). Conclusion: Using the indirect method, TSH RI in the Lebanese population is wider than the manufacturers'one and that those obtained by the direct method and varies according to age, gender and over time. A periodic reevaluation of RI for each population should be done.